Green supply chain in a Colombian textile company (2017)
This article aims to enunciate some logistic practices within the process of selection and evaluation of suppliers in a company of the textile sector in Bogotá. We hope to contribute to the improvement of the current process, through the inclusion of environmental factors and the determination of key strategies for converting local suppliers into global.